High-Throughput CRISPR/Cas9 Mutagenesis Streamlines Trait Gene Identification in Maize. Issue 5 (25th February 2020) - Liu, Hai-Jun; Jian, Liumei; Xu, Jieting; Zhang, Qinghua; Zhang, Maolin; Jin, Minliang; Peng, Yong; Yan, Jiali; Han, Baozhu; Liu, Jie; Gao, Fan; Liu, Xiangguo; et al.
Abstract : Applying an improved high-throughput gene-editing pipeline to functionally mapped candidates promises high-efficiency gene discovery by large-scale knowledge-informed mutagenesis. Abstract: Maize ( Zea mays ) is one of the most important crops in the world. However, few agronomically important maize genes have been cloned and used for trait improvement, due to its complex genome and genetic architecture. Here, we integrated multiplexed CRISPR/Cas9-based high-throughput targeted mutagenesis with genetic mapping and genomic approaches to successfully target 743 candidate genes corresponding to traits relevant for agronomy and nutrition. After low-cost barcode-based deep sequencing, 412 edited sequences covering 118 genes were precisely identified from individuals showing clear phenotypic changes. The profiles of the associated gene-editing events were similar to those identified in human cell lines and consequently are predictable using an existing algorithm originally designed for human studies. We observed unexpected but frequent homology-directed repair through endogenous templates that was likely caused by spatial contact between distinct chromosomes. Based on the characterization and interpretation of gene function from several examples, we demonstrate that the integration of forward and reverse genetics via a targeted mutagenesis library promises rapid validation of important agronomic genes for crops with complex genomes. Beyond specific findings, this study also guides further optimization of high-throughput CRISPR experiments in plants.